Precommitment of CD4+CD8+Thymocytes to Either CD4 or CD8 Lineages - Crompton, T; Lees, R K; Pircher, H; MacDonald, H R (Proceedings of the National Academy of Sciences - PNAS, 1993)
CD4+and CD8+mature T cells arise from CD4+CD8+precursors in the thymus. During this process, cells expressing T-cell receptors (TCRs) reactive with self major histocompatibility complex (MHC) class I or II molecules are positively selected to the CD8 or CD4 lineage, respectively. It is controversial whether lineage commitment of CD4+CD8+thymocytes is controlled directly by TCR specificity for MHC (instructional model) or, alternatively, by processes that operate independently of TCR specificity (stochastic model). We show here that CD4+CD8+thymocytes bearing a MHC class I-restricted transgenic TCR can be subject to two alternative developmental fates. One population of CD4+CD8+cells is positively selected by MHC class I molecules to the CD8 lineage as expected, whereas the other CD4+CD8+population rearranges endogenous TCR genes and is positively selected by MHC class II molecules to the CD4 lineage. Blocking TCR-MHC class II interactions in vivo does not interfere with the generation of CD4+CD8+cells expressing endogenous TCRs but does prevent their subsequent maturation to CD4+cells. These data support a version of the stochastic model in which CD4+CD8+thymocytes are precommitted to the CD4 or CD8 lineage independently of TCR specificity for MHC and prior to positive selection.